A geomining theme park in the Vetas-California mining district (Santander): An integrated approach for assessing the geotourism and geoeducation potential - Pardavé Livia, Walter (2023)
The province of Soto Norte (Santander), Colombia, is known for its mining tradition in the municipalities of Vetas and California. Four centuries ago, mining exploitation was developed and environmental liabilities were generated, which put at risk in activity. Many defend the topographic and vegetal restoration of exhausted mining operations, burying them or sealing them. However, when these works have brought out mineral outcrops of worldwide interest or have allowed access to galleries excavated many centuries ago that have provided valuable archaeological remains that have served to learn a little more about our history. Therefore, in the face of the generally accepted idea that the restoration of a mining waste inevitably passes through its burial or sealing. Geotourism around the mining industry is an emerging sector that contributes not only to the diffusion of the interesting geological and mining heritage of the Vetas-California mining district (Santander), Colombia, but also to the development of local communities. Therefore, this mining district can be transformed in a geomining thematic park to protect the natural resources and to promote the growth of the local, regional and national economy.